THE EFFECT OF LONG FISHING TRIP, VESSEL SIZE, SIZE MACHINES AND AGE OF MACHINE TO THE AMOUNT OF FUEL CARRIED FISHING VESSEL SONDONG IN PPI DUMAI - Lisnasari, Esy; Zain, Jonny; Syofyan, Irwandy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on March 2015 at held at Fish Landing Base(PPI) Dumai Pangkalan Sesai Regency, Dumai Barat Subdistrict, Dumai City inMarch 2015. The puropse is find formula total of fuel must carried fishing vesselof sondong. The method used is survey method. From the analisis correlationresults obtained among total of fuel carried by vessel size, engine size anda enginelife is Y = 193,391 – 14,205X1 + 0,419X2 – 2,120X3. But the correlation is weak,because fisherman of sondong buy of fuel only be based ability strengthpurcasing.Keywords: vessel sondong, fuel, fishing trip, vessel size, engine size, engine life